Nanoscaled buffering zone of charged (PLGA)(n)-b-bPEI micelles in acidic microclimate for potential protein delivery application - Kang, Han Chang (2012)
Poly(lactide-co-glycolide) (PLGA) has most often been employed for the controlled release of protein formulations because of its safety profile with non-toxic degradation products. Nevertheless, such formulations have been plagued by a local acidic microenvironment and protein-polymer interactions, which result in chemical and physical denaturation of loaded proteins and often unfavorable release profiles. This study investigated the pH change of inner PLGA microsphere (MS) using charged (PLGA)(n)-b-branched polyethyleneimine (bPEI) micelles. The designed micelles can be transformed into either micelle or reverse micelle (RM) depending on the solvent and RM can form microspheres. In addition, (PLGA)(n)-b-bPEI can be modified into (PLGA)(n)-b-(carboxylated bPEI) via carboxylation of the primary amines. Cationic micelle (CM) or anionic micelle (AM) were complexed with counter-charged proteins leading to nanosized particles (approximately 100 nm). In the micelle/protein complexes, the micelles mostly maintained their proton buffering capacity, and consequently, prevented or delayed the typical decrease in pH caused by degradation of PLGA in aqueous solution. Reconstitutable micelle/protein complexes allowed for increased and fine-tuned protein loading (~20 wt% when using CM1 (CM prepared from PLGA(36kDa)-b-bPEI(25kDa))/insulin complexes) in PLGA MS. In CM2 (CM prepared from (PLGA(36kDa))(2)-b-bPEI(25kDa))/insulin (4 of weight ratio (WR) of micelle to protein; WR4)-loaded PLGA MS, CM2 strongly prevented the micellar nanoenvironmental pH (pH 6.6 within 5 days and then approximately pH 8.5) to be acidified in PLGA MS for 9 weeks, unlike CM2-free PLGA MS. In conclusion, our findings propose that the proton buffering capacity and protein loading in PLGA MS can be tuned by controlling the complexation ratios of micelles and proteins, polymeric architectures of (PLGA)(n)-b-bPEI copolymers and WR of micelle/protein complexes and PLGA (or RM).